The Influence of Ethical Leadership on Teachers' Professional Commitment: The Mediating Role of Organizational Culture in Public Universities in Addis Ababa - Koyira, Zewdie Zakie Koyira (African Journal of Leadership and Development, 2024)
This study investigated the impact of ethical leadership on teachers' professional commitment, specifically examining the mediating role of organizational culture within public universities in Addis Ababa. Employing a descriptive research design with a deductive approach, data was collected from 384 teachers across four universities using proportionate random sampling. A 95-item standardized questionnaire assessed teachers' professional commitment (TPC), ethical leadership (EL), and organizational culture (OC). Statistical analysis, including descriptive and inferential methods, was conducted using Jamovi software. The results confirmed all direct hypotheses and validated organizational culture's mediating role between ethical leadership and teachers' professional commitment. Significant positive effects were found for ethical leadership on both teachers' professional commitment and organizational culture, as well as for organizational culture on teachers' professional commitment. These findings underscore the necessity for universities to address demographic factors and enhance work conditions to bolster teacher commitment. University leaders are urged to prioritize ethical standards and cultivate a positive organizational culture. This research highlights the pivotal role of ethical leadership and organizational culture in educational settings, providing valuable insights for leaders, policymakers, program designers, and researchers. It contributes to organizational management literature by illustrating how teachers' professional commitment can be fostered through these elements. Further longitudinal studies are recommended to deepen understanding of these relationships.